2018
DOI: 10.1016/j.ccell.2018.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis of Genetic Ancestry and Genomic Alterations across Cancers

Abstract: SUMMARY Disparities in cancer care have been a long-standing challenge. We estimated the genetic ancestry of The Cancer Genome Atlas patients, and performed a pan-cancer analysis on the influence of genetic ancestry on genomic alterations. Compared with European Americans, African Americans (AA) with breast, head and neck, and endometrial cancers exhibit a higher level of chromosomal instability, while a lower level of chromosomal instability was observed in AAs with kidney cancers. The frequencies of TP53 mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
196
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 201 publications
(209 citation statements)
references
References 62 publications
13
196
0
Order By: Relevance
“…In 2005, investigators showed a 99.9% concordance between SIRE and genetically derived clusters for 3,636 individuals from four racial/ethnic groups groups 50 , and a 2007 study reported 100% classification accuracy of individuals from geographically separated population groups when thousands of genetic variants were used for clustering 51 . More recently, a study of >11,000 cancer patients from The Cancer Genome Atlas found an 95.6% concordance between self-reported race (not ethnicity) and GA 52 , and a massive study of >200,000 individuals from the Million Veterans Program found >99.4% concordance between SIRE and GA 53 . The latter two studies relied on machine learning classifiers powered by vectors of 7 and 30 ancestry principal components, respectively, whereas our clustering algorithm uses vectors of only three continental ancestry components to classify individual genomes.…”
Section: Concordance Between Sire and Ga In The Usmentioning
confidence: 99%
“…In 2005, investigators showed a 99.9% concordance between SIRE and genetically derived clusters for 3,636 individuals from four racial/ethnic groups groups 50 , and a 2007 study reported 100% classification accuracy of individuals from geographically separated population groups when thousands of genetic variants were used for clustering 51 . More recently, a study of >11,000 cancer patients from The Cancer Genome Atlas found an 95.6% concordance between self-reported race (not ethnicity) and GA 52 , and a massive study of >200,000 individuals from the Million Veterans Program found >99.4% concordance between SIRE and GA 53 . The latter two studies relied on machine learning classifiers powered by vectors of 7 and 30 ancestry principal components, respectively, whereas our clustering algorithm uses vectors of only three continental ancestry components to classify individual genomes.…”
Section: Concordance Between Sire and Ga In The Usmentioning
confidence: 99%
“…19 To define the AA and EA patient groups, data from the Cancer Genome Ancestry Atlas (TCGAA) 11 were used. Because the SEER database lacks comprehensive sociodemographic information, a secondary survival analysis using data from the National Cancer Database (NCDB), another US cancer registry, was performed.…”
Section: Data Sourcesmentioning
confidence: 99%
“…These survival data were paired with molecular data from The Cancer Genome Atlas (TCGA). 19 To define the AA and EA patient groups, data from the Cancer Genome Ancestry Atlas (TCGAA) 11 were used. TCGA contains data such as clinical information, histopathology, and molecular information derived from information on samples obtained from more than 11,000 patients.…”
Section: Data Sourcesmentioning
confidence: 99%
See 2 more Smart Citations